Kirigami Patterning of MXene/Bacterial Cellulose Composite Paper for All‐Solid‐State Stretchable Micro‐Supercapacitor Arrays. Issue 12 (12th April 2019) - Jiao, Shangqing; Zhou, Aiguo; Wu, Mingzai; Hu, Haibo
Abstract: Stretchable micropower sources with high energy density and stability under repeated tensile deformation are key components of flexible/wearable microelectronics. Herein, through the combination of strain engineering and modulation of the interlayer spacing, freestanding and lightweight MXene/bacterial cellulose (BC) composite papers with excellent mechanical stability and a high electrochemical performance are first designed and prepared via a facile all‐solution‐based paper‐making process. Following a simple laser‐cutting kirigami patterning process, bendable, twistable, and stretchable all‐solid‐state micro‐supercapacitor arrays (MSCAs) are further fabricated. As expected, benefiting from the high‐performance MXene/BC composite electrodes and rational sectional structural design, the resulting kirigami MSCAs exhibit a high areal capacitance of 111.5 mF cm −2, and are stable upon stretching of up to 100% elongation, and in bent or twisted states. The demonstrated combination of an all‐solution‐based MXene/BC composite paper‐making method and an easily manipulated laser‐cutting kirigami patterning technique enables the fabrication of MXene‐based deformable all‐solid‐state planar MSCAs in a simple and efficient manner while achieving excellent areal performance metrics and high stretchability, making them promising micropower sources that are compatible with flexible/wearable microelectronics. Abstract : The demonstrated combination of an all‐solution‐based MXene/bacterial cellulose composite paper‐making method and easily manipulated laser‐cutting kirigami patterning technique enables the fabrication of MXene‐based all‐solid‐state stretchable micro‐supercapacitor arrays in a simple and efficient manner while achieving both a high areal capacitance of 111.5 mF cm −2 and a high elongation of 100%, making them promising compatible micropower sources for flexible/wearable microelectronics.